Studi Topografi Dasar Laut di Kawasan Pesisir Perairan Desa Penyak, Kabupaten Bangka Tengah - Slamet, Slamet Kristianto; Akhrianti, Irma; Hudatwi, Mu’alimah (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2023)
Penyak Village is one of the villages located in the Koba sub-district, Central Bangka Regency. This village is one of the villages directly adjacent to the Karimata Strait. There is a fairly long coastline of up to 3 km and structures the (breakwaters) along the coastal waters. The relationship among bathymetry, abrasion-accretion and breakwater is the occurrence of coastline reduction and coastline additions that occur along the waters. The method used in this research is primary data and secondary data. Primary data is taken directly at the research location, namely bathymetry data. And the secondary data used as research supporting data, namely tidal data. The research results show that the waters of Penyak Village have a depth of 4.4 to -0.8 m, calculated with the LLWL reference displayed on the 3D map. Tidal data is processed using the Admiralty formula, producing 9 tidal harmonic values and determining the LLWL (lower low water level) value of 16 cm, the Z0 (The height of the receding face) value of 130 cm, the HHWL (Higher High Water Level) value of 270, the MSL (Mean sea level) of 143 cm, and the Form-zahl value is 9.14. The type of tide obtained from the management of the Admiralty Formula is a single daily tide type (diurnal tide). Where in one day there is one high tide and one low tide.